2018
DOI: 10.3390/ijms19061567
|View full text |Cite
|
Sign up to set email alerts
|

Luteolin-Mediated Inhibition of Hepatic Stellate Cell Activation via Suppression of the STAT3 Pathway

Abstract: Hepatic stellate cell (HSC) activation is responsible for hepatic fibrogenesis and is associated with an overexpression of transcription 3 (STAT3). Luteolin, a common dietary flavonoid with potent anti-inflammatory properties, has previously demonstrated antifibrogenic properties in HSCs but the mechanism has not been fully elucidated. Activated human and rat hepatic stellate cell lines LX-2 and HSC-T6 were used to study the effects of luteolin on HSCs. Cellular proteins were determined by western blot and imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…After luteolin treatment, IL-6 affected either STAT3 phosphorylation or HO-1 expression was inhibited ( Figure 7B). A recent study indicated that luteolin treatment blocked STAT3 phosphorylation in hepatic stellate cells to attenuate the expression of STAT3-regulated proteins, which is in agreement with our study [57]. Similar results from the reporter assays confirmed that both AG490 and luteolin could downregulate IL-6-stimulated HO-1 expression in HepG2 cells (Figure 7).…”
Section: Discussionsupporting
confidence: 92%
“…After luteolin treatment, IL-6 affected either STAT3 phosphorylation or HO-1 expression was inhibited ( Figure 7B). A recent study indicated that luteolin treatment blocked STAT3 phosphorylation in hepatic stellate cells to attenuate the expression of STAT3-regulated proteins, which is in agreement with our study [57]. Similar results from the reporter assays confirmed that both AG490 and luteolin could downregulate IL-6-stimulated HO-1 expression in HepG2 cells (Figure 7).…”
Section: Discussionsupporting
confidence: 92%
“…The sample that was not treated with luteolin was employed as the control. The mixture was incubated at 37 ºC at a speed of 150 rpm and the absorption of the bacterial suspension at 600 nm was measured after 2,4,8,12,16,20,24,28,32,36, and 40 h of incubation. The bacterial growth curve was plotted to analyse the effect of luteolin on T. pyogenes growth.…”
Section: Determination Of the Growth Curvementioning
confidence: 99%
“…Luteolin exerts its anti-inflammatory effects partly by regulating inflammatory mediators and different cytokines, which inhibit the signal transduction pathway. [19][20][21][22] Luteolin could hamper the progression of cancer through multiple mechanisms including the suppression of kinases, regulation of cell cycle, induction of apoptotic cell death, and reduction of transcription factors. [23][24][25][26] Many researchers have focused on the antiinflammatory and anti-tumour properties of luteolin; however, only minor attention has been paid to its good antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported inhibiting STAT3 pathway could exerts anti-inflammatory and anti-oxidative effect [19]. Lut has the ability to inhibit hepatic fibrosis through suppression of the STAT3 pathway [12]. Besides, increasingly number of researches have demonstrated the STAT3 was the potential target of Lut [38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Renal fibrosis is the basic pathological manifestation of many chronic kidney diseases(CKD) and delaying renal fibrosis is an effective treatment for CKD [11]. The action mechanism of Lut varies, but the nuclear factor (NF)-κB pathway, MAPK in the activator protein (AP)-1 pathway, and signal transducer and activator of transcription 3 (STAT3) pathway are its major target transcription factors [12,13]. In this study, we mainly focused on STAT3 pathway because it was significantly suppressed by Lut compared with NF-κB and AP-1 in our preliminary experiment.STAT3 is an important member of the STAT family and mediates cell survival and proliferation [14].…”
Section: Introductionmentioning
confidence: 99%